2011
DOI: 10.1016/j.pharmthera.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein mimetic peptides: Mechanisms of action as anti-atherogenic agents

Abstract: Apolipoprotein mimetic peptides are short synthetic peptides that share structural, as well as biological features of native apolipoproteins. The early positive clinical trials of intravaenous preparations of apoA-I, the main protein component of high density lipoproteins (HDL), have stimulated great interest in the use of apolipoprotein mimetic peptides as possible therapeutic agents. Currently, there are a wide variety of apolipoprotein mimetic peptides at various stages of drug development. These peptides t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 104 publications
0
65
0
Order By: Relevance
“…Thus, there has been considerable interest in employing a design approach that involves shorter peptides that mimic apoA-I ( 21 ). From numerous studies on apoA-I mimetic peptides based on one or two amphiphilic ␣ -helical segments (22)(23)(24)(25)(26), a wide range of peptide sequences have been found that are more-or-less effective in various aspects of apoA-I mimicry. Many of these peptides have no sequence homology to apoA-I, as they capitalize on an amphiphilic ␣ -helical structural motif, and some are composed of all D -amino acids ( 21 ).…”
Section: In Vivo Effi Cacymentioning
confidence: 99%
“…Thus, there has been considerable interest in employing a design approach that involves shorter peptides that mimic apoA-I ( 21 ). From numerous studies on apoA-I mimetic peptides based on one or two amphiphilic ␣ -helical segments (22)(23)(24)(25)(26), a wide range of peptide sequences have been found that are more-or-less effective in various aspects of apoA-I mimicry. Many of these peptides have no sequence homology to apoA-I, as they capitalize on an amphiphilic ␣ -helical structural motif, and some are composed of all D -amino acids ( 21 ).…”
Section: In Vivo Effi Cacymentioning
confidence: 99%
“…In addition to its role in reverse cholesterol transport, HDL particles have increasingly been recognized to modulate innate and adaptive immune responses, as well as to have antiinflammatory, antioxidant, antithrombotic, and antifibrotic properties. [6][7][8] This Ahead of the Curve article reviews the evidence supporting the concept of developing apoA-I mimetic peptides for the treatment of asthma.…”
mentioning
confidence: 99%
“…apoA-I is a key component of highdensity lipoprotein (HDL) particles that mediates reverse cholesterol transport out of cells and thereby protects against atherosclerosis (11,12). Cholesterol is transported out of cells by interactions between HDL and the ATP-binding cassette (ABC), subfamily A, member 1 (ABCA1), as well as other transporters, such as ABCG1 and SR-BI (12).…”
mentioning
confidence: 99%
“…Cholesterol is transported out of cells by interactions between HDL and the ATP-binding cassette (ABC), subfamily A, member 1 (ABCA1), as well as other transporters, such as ABCG1 and SR-BI (12). Furthermore, the ability of endothelial cells to bind, internalize, and transcytose lipidfree apoA-I is mediated by ABCA1 (13).…”
mentioning
confidence: 99%